Water and Wastewater Services in the Danube Region : Ukraine Country Note - World Bank (Washington, DC, 2015)
To evaluate and reflect the sustainability of services in the region, an overall sector sustainability assessment was done, taking into account four main dimensions: access to services, quality of services, efficiency of services, and financing of services. Each of these dimensions is measured through three simple and objective indicators. For each indicator, best practice values are established by looking at the best performers in the region, and countries closest to those best performers are deemed to have a more mature sector. A more complete description of the methodology to assess sector sustainability is included in the Annex of the State of the Sector Regional Report from the Danube Water Program. The outcomes of this assessment for the Ukraine water sector are shown in Figure 10, which also shows average and best practices in the Danube region. The Ukrainian sector sustainability score is 54, which is below the Danube average sustainability of 64. The assessment shows that, on average, the country performs well in terms of collection ratio and affordability. The main deficiencies of the Ukraine water sector identified through the sector sustainability assessment are investment level, wastewater treatment coverage, and nonrevenue water. The main sector challenges are: improving and clarifying the legal regulatory framework of the water sector; ensuring tariff setting according to the cost recovery principle to improve overall efficiency; and improving staff capacities and expertise.